Analysis of Islamic Religious Education (PAI) Problems and Solutions in Facing the Development of the 21st Century (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
In the development of the 21st century, Islamic religious education faces a number of challenges that need to be overcome. It can be seen that the lack of adequate facilities, such as reading books, causes students' disinterest in reading, the accuracy of using learning methods, and the like. The purpose of the study is (1) to find and describe the problems of Islamic religious education (2) analyze these problems, especially in Islamic religious education in the 21st century. Then, the type used in this study is using a qualitative approach with library research methods. The gains in this study from the forms of problems and solutions in Islamic religious education (PAI) in the development of the 21st Century are: First, internal problems (1) mastery of the material, (2) love the teaching profession, (3) skills in teaching, (4) evaluate student learning. Second, external problems (1) managing classes, (2) applying learning methods and models, (3) lack of teacher interaction with students, (4) utilization of learning media. So, to overcome these problems, a comprehensive and holistic approach is needed. Then it also takes strong collaboration between educational institutions, government, and other parties to be able to form a relevant curriculum in accordance with the times. Furthermore, the researcher provides suggestions for the next author to study more deeply and comprehensively about the problems of Islamic religious education in the 21st century. Especially on the causal factors and implications in learning through the use of technology.